Cerebral and aortic aneurysms in electroconvulsive therapy patients: a systematic review and results from 12 years of screening - Ullrich, Heiko; Sartorius, Alexander; Karl, Sebastian (The journal of ECT, 2024)
Introduction - Theoretically, the procedural risk of electroconvulsive therapy (ECT) could be increased in the presence of undetected aneurysms due to the hemodynamic changes associated with ECT. However, empirical evidence is limited to few individual case reports and case series. - Methods - We performed a systematic review of available evidence on ECT treatment in patients with intracranial aneurysms and untreated aortic aneurysms and we retrospectively analyzed data from 252 consecutive patients referred for ECT at the Department of Psychiatry, Psychotherapy and Psychosomatics of Siegen Hospital, Germany, who received magnetic resonance angiographies and abdominal sonographies as part of their routine pre-ECT workup. - Results - Of 252 patients referred for ECT, 5 (2.0%) were found to have an intracerebral aneurysm and 1 (0.4%) was found to have an abdominal aortic aneurysm. These cases are reported in detail together with 2 additional cases of aortic aneurysms from the Central Institute of Mental Health, Mannheim, Germany. Electroconvulsive therapy was performed without complications in all 8 cases. - Conclusions - Aneurysms might occur in ECT patients at a similar rate as in the general population. The number of ECTs performed annually in mostly unscreened patients suggests that there might be a significant number of patients with undetected aneurysms in whom ECT is performed without reported complications.
Gesehen am 24.04.2025